Computer Science in the Management of Operating Theatres: A Challenge for Sub-Saharan Anaesthetists and Resuscitation Medical Doctors - Diedhiou, M.; Tendeng, JN.; Barboza, D.; Diallo, A. K.; Diao, ML.; Camara, G.; Konate, I. (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Anesthetists and resuscitation doctors often coordinate the management of operating theaters. Information systems that are an importants tools for operating theatre management are not commonly used in Senegal. The objective of this study is to evaluate the contribution of computer sciences in improving the management and quality of care in the operating theatre. Material and Method: Prospective evaluation over one year of the quality of the standardized discharge summaries (anaesthetic and surgical protocols) provided by the SIMENS software based on the analysis of a Hospital Information System (HIS) use indicators: comprehensiveness, completeness, and validity. Results: The overall comprehensiveness on the use of the Information System (IS) in the Operative Room (OR) was 89%, the completeness of the fields was optimal in 96.6% of the cases for the operating protocols and in 80% of the cases for the anesthetic protocols. 64% of the anesthetic protocols were considered valid compared to 73.3% validity for the surgical protocols. Discussion/Conclusion: The computerization of operating theatres is a long-term process and will ultimately improve the quality of care by having an impact on quality management. Improving the indicators of practical use of an IS in the operating theatre (comprehensiveness, completeness and validity of RSS) requires good involvement of all actors of the theatre environment. The benefits of computerization would be more relevant once the services associated with the operating theatre (hospital services, stretcher-boarding, etc.) are connected to the computer system, but also by automating the input of information to be included in anaesthetic and surgical protocols.